How Does Developing Enforcement Capacity Reduce Wildlife Crime? Increa sing program effectiveness by understanding common assumptions - Price, Claire; Buff, Jesse; Peabody, Shawn; Present, Tess; Lauck, Liz (USAID, 2018)
"How Does Developing Enforcement Capacity Reduce Wildlife Crime?" summ arizes findings from the literature around four key assumptions about capacity building for enforcement and prosecution. Using the experienc es and evidence summarized in this brief, program designers and implem enting partners should be able to increase the effectiveness and effic iency of their capacity building efforts.